2023
DOI: 10.1002/adma.202300487
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, High‐Strain, and Strong Uniaxial Hydrogel Actuators from Recyclable Nanofibril Networks

Abstract: Polymer hydrogels mimic biological tissues and are suitable for future lifelike machines. However, their actuation is isotropic, so they must be crosslinked or placed in a turgor membrane to achieve high actuation pressures, severely impeding their performance. Here, it is shown that organizing cellulose nanofibrils (CNFs) in anisotropic hydrogel sheets leads to mechanical in-plane reinforcement that generates a uniaxial, out-of-plane strain with performance far surpassing polymer hydrogels. These fibrillar hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…[27] To increase the actuation rate, we envision tuning the type of electrolyte and its concentration, reduce the cohesion in the network, or design of advanced structures with channels or holes to provide faster access to the electrolyte locally, which has been shown to improve the actuation rate of CNF sheets. [14] Thanks to the abundance of CNFs and bulk electroactive nanomaterials, our multifunctional hydrogels can be easily produced in any lab and at scale. CNF nanocomposites can be shaped into advanced 3D objects, such as extruded threads or 3D-printed patterns, [36,37] taking us one step toward realizing soft intelligent systems where actuation, sensing, permeability control, and, in the future, ionotronic computation [3] are monolithically embedded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] To increase the actuation rate, we envision tuning the type of electrolyte and its concentration, reduce the cohesion in the network, or design of advanced structures with channels or holes to provide faster access to the electrolyte locally, which has been shown to improve the actuation rate of CNF sheets. [14] Thanks to the abundance of CNFs and bulk electroactive nanomaterials, our multifunctional hydrogels can be easily produced in any lab and at scale. CNF nanocomposites can be shaped into advanced 3D objects, such as extruded threads or 3D-printed patterns, [36,37] taking us one step toward realizing soft intelligent systems where actuation, sensing, permeability control, and, in the future, ionotronic computation [3] are monolithically embedded.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the fastest hydrogel actuators can be achieved by anisotropic fibrillar hydrogels, where the uniaxial expansion leads to fast and high strain. [ 14 ] Like these examples, most hydrogel actuators only activate or speed up a passive, diffusion‐limited swelling mechanism using, often irreversible, stimulations. Electronic control of hydrogel fibers was previously achieved by pH changes due to electrolysis around an embedded metal electrode at high voltage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Benselfelt et al found that the anisotropic cellulose nanofibril (CNF) hydrogel sheets exhibited uniaxial, out-of-plane actuation that far surpassing other polymer hydrogels. 156 Subsequently, they demonstrated an electrochemically actuated composite hydrogel consisting of carbon nanotubes (CNT) and CNF, featuring high in-plane conductivity and precise control of shape-morphing at just 1 V. 157 This innovative materials system achieved remarkable electroactive pressure and work density, thus enabling advanced soft intelligent systems with integrated actuation, sensing, and controlled permeation. Another interesting example is the nanocomposite membrane proposed by Tian et al based on 1D flexible nanofibrous cellulose and 2D Ti 3 C 2 T x MXene with high aspect ratio and electrification.…”
Section: Electrode Designmentioning
confidence: 99%
“…The composites thus provide precise electronic control compared with high‐performance actuators from neat CNF sheets. [ 22 ] This new class of materials provides many possibilities for actuation, tunable membranes, sensors, artificial muscles, and beyond.…”
Section: Introductionmentioning
confidence: 99%